2015
DOI: 10.1371/journal.pone.0126842
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Intima-Media Thickness and Aortic Diameter in Small for Gestational Age and Growth Restricted Fetuses

Abstract: ObjectiveThe objective of this study is to measure aortic intima-media thickness (aIMT) and aortic diameter (AD) in appropriate for gestational age (AGA) fetuses, small for gestational age (SGA) fetuses, and intrauterine growth restricted (IUGR) fetuses.MethodsCase-control study performed between June 2011 and June 2012. Forty-nine AGA fetuses, 40 SGA fetuses, and 35 IUGR fetuses underwent concomitant measurement of aIMT and AD at a mean gestational age of 34.4 weeks.ResultsMedian aIMT was higher in fetuses wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…The intima-media thickness (IMT) and the stiffness of the abdominal aorta by means of ultrasound examination are the most promising non-invasive biomarkers of adverse cardiovascular remodeling in fetuses and newborns [3,[6][7][8][9][10][11][12]. Fetal aortic IMT might be related to inflammation, probably indicating a very early stage of future atherosclerosis in adulthood [13].…”
Section: Introductionmentioning
confidence: 99%
“…The intima-media thickness (IMT) and the stiffness of the abdominal aorta by means of ultrasound examination are the most promising non-invasive biomarkers of adverse cardiovascular remodeling in fetuses and newborns [3,[6][7][8][9][10][11][12]. Fetal aortic IMT might be related to inflammation, probably indicating a very early stage of future atherosclerosis in adulthood [13].…”
Section: Introductionmentioning
confidence: 99%
“…Low birth weight and Doppler abnormalities in IUGR have been proposed to alter vascular structure causing possible endothelial damage [5]. Interestingly, a higher median aortic wall intima-media thickening has been shown in IUGR compared to SGA fetuses as a potential sign of preclinical atherosclerosis, which might predispose these individuals to later cardiovascular disease [10] and which underlines the importance to clearly differentiate between IUGR and SGA.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial distensibility is commonly measured as the relative systolic increase in arterial volume, and reflects the mechanical load placed on the arterial wall, while compliance refers to the unit change in volume induced by a unit change in pressure, and reflects the artery's ability to store volume thus limiting pressure rises (buffering function) . In addition to arterial elasticity, intima‐media thickness (IMT) of the abdominal aorta is also a well‐established marker for CVD risk in young adults and children …”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] In addition to arterial elasticity, intima-media thickness (IMT) of the abdominal aorta is also a well-established marker for CVD risk in young adults and children. [21][22][23][24] To date, there is little research describing distal abdominal aorta compliance and distensibility in fetuses, in general, and especially in those exposed to maternal diabetes. Hu and co-authors 25 reported differences in pulse wave velocity (PWV), an indirect measure of elasticity, between fetuses of insulin-dependent diabetic mothers and fetuses of non-diabetic mothers.…”
Section: Introductionmentioning
confidence: 99%